Synthesis of C2-Methylene Glycitols from 1,2-Cyclopropanated Sugars: En Route to Iminosugar Analogues - Seshadri, Kalapati; Sridhar, Perali Ramu (Synthesis, 2014)
C2-Methylene glycitols were synthesized in three steps by halonium ion mediated solvolytic ring opening of 1,2-cyclopropanated sugars, dehydrohalogenation using potassium carbonate in aqueous acetonitrile, and reduction with sodium borohydride. The generality of the methodology was evaluated by applying it to a series of 1,2-cyclopropanated pyranoses as well as furanoses to give the corresponding C2-methylene glycitol derivatives. Furthermore, the obtained glycitols were converted into 1-deoxy-C2-methylene iminosugar derivatives.
Keywords: azasugars; carbohydrates; electrophilic addition; piperidines; cyclization